“Oscillate Wildly”: Morrissey’s art and persona as a continuation of Oscar Wilde’s artistic legacy - Adamskich, Karolina (Scripta Neophilologica Posnaniensia, 2020)
The works of Oscar Wilde form a link between late Victorian and modernist literature. His art and wit have continued to exert a great influence on other artists. The art of Morrissey, a legendary poet and singer, may serve as a case in point. Thus, this paper aims at presenting Morrissey’s works and persona as a continuation of Oscar Wilde’s artistic legacy. The article presents their attitude to life and to the process of creation. In view of that, breaking with traditional moral code, the artists’ fascination with beauty, their defense of humanity and all possible freedoms, as well as earnestness of their works, is depicted as the key to the analysis of their art. Thus, the writers’ rebellion against society and modern life, along with propounding aestheticism, will be investigated in this paper